Enantiodivergent Kinetic Resolution of 1, 1′‐Biaryl‐2, 2′‐Diols and Amino Alcohols by Dipeptide‐Phosphonium Salt Catalysis Inspired by the Atherton–Todd Reaction. (5th May 2021) - Fang, Siqiang; Tan, Jian‐Ping; Pan, Jianke; Zhang, Hongkui; Chen, Yuan; Ren, Xiaoyu; Wang, Tianli
Abstract: A highly enantiodivergent organocatalytic method is disclosed for the synthesis of atropisomeric biaryls via kinetic resolution inspired by a dipeptide‐phosphonium salt‐catalyzed Atherton–Todd (A‐T) reaction. This flexible approach led to both R ‐ and S ‐enantiomers by fine‐tuning of bifunctional phosphonium with excellent selectivity factors ( s ) of up to 1057 and 525, respectively. The potential of newly synthesized O‐phosphorylated biaryl diols was illustrated by the synthesis of axially chiral organophosphorus compounds. Mechanistic investigations suggest that the bifunctional phosphonium halide catalyst differentiates between the in‐situ‐generated P‐species in the A‐T process, mainly involving phosphoryl chloride and phosphoric anhydride, thus leading to highly enantiodivergent O‐phosphorylation reactions. Furthermore hydrogen bonding interactions between the catalysts and phosphorus molecules were crucial in asymmetric induction. Abstract : An enantiodivergent organocatalytic kinetic resolution method has been developed, which is inspired by the Atherton–Todd (A‐T) reaction. A range of R ‐ and S ‐enantiomers of atropisomeric biaryls were obtained in high yields with excellent selectivity factors. The bifunctional phosphonium halide catalysts differentiate between the in‐situ‐generated P ‐species in the A‐T reaction system, which results in efficient enantiodivergent O‐phosphorylation reactions.